Systematic Review of Hepatitis C Virus Prevalence in the WHO Western Pacific Region - Jenny Iversen; Handan Wand; Po-Lin Chan; Linh-Vi Le; Lisa Maher (Viruses, 2022)
Background: This review aimed to identify hepatitis C virus (HCV) prevalence estimates among the general population and six key populations (people who inject drugs, men who have sex with men, sex workers, prisoners/detainees, Indigenous people, and migrants) in the World Health Organization Western Pacific Region (WHO WPR). Methods: Original research articles published between 2016 and 2020 were identified from bibliographic databases. Publications were retrieved, replicas removed, and abstracts screened. Retained full texts were assessed and excluded if inclusion criteria were not met. Methodological quality was assessed using the Johanna Briggs Institute critical appraisal checklist for prevalence data. Data on HCV exposure and active infection were extracted and aggregated and forest plots generated for each population by country. Results: There were no HCV prevalence estimates in any population for more than half of WPR countries and territories. Among the 76 estimates, 97% presented prevalence of exposure and 33% prevalence of active infection. General population viraemic prevalence was 1% or less, except in Mongolia. Results confirm the endemic nature of HCV among people who inject drugs, with estimates of exposure ranging from 30% in Cambodia to 76% in Hong Kong. Conclusions: Countries require detailed knowledge of HCV prevalence in diverse populations to evaluate the impact of efforts to support WHO HCV elimination goals. Results provide baseline estimates from which to monitor and evaluate progress and by which to benchmark future elimination efforts.